Positive Effect of Chewing Gum and Early Mobilization on Intestinal Peristalsis - Daffa Basandra Putra; Taufan Arif; Tri Cahyo Sepdianto; Maria Diah Ciptaningtyas (STIKes Patria Husada Blitar, 2023)
Decreased intestinal peristalsis due to anesthesia before laparotomy surgery can result in inhibition of nerve impulses to the intestinal muscles, paralytic ileus can occur and inhibition of the work of the intestine itself. The purpose of this study was to determine the effect of chewing gum and early mobilization on intestinal peristalsis after laparotomy surgery. The research design used a quasi-experimental. The sampling technique used purposive sampling with 32 respondents divided into 2 groups. The treatment group was given an intervention of chewing gum and early mobilization, while the control group was given an intervention according to standard operating hospital procedures, namely tilting right and left and given 2 spoons of drinking after the patient was fully conscious in the room. The independent variables were chewing gum and early mobilization. The dependent variable was intestinal peristaltic. This study used univariate analysis to determine the characteristics of respondents. The bivariate analysis used paired t test and independent t test. The paired t test in the pre-posttest in the control group was 0.000, while the pre-posttest in the treatment group was 0.000. Independent T test on the post-test of the treatment group with the post-test of the control group of 0.000. There was an effect of chewing gum and early mobilization intervention on intestinal peristalsis in post laparotomy patients. Chewing gum and early mobilization can stimulate hormones in the gastrointestinal system such as gastrin, secretin, gastric inhibitory polypeptide, cholecystokinin, motilin, and enteroglukagon which will increase intestinal peristalsis